Bioactive profiling and evaluation of anti-proliferative and anti-cancerous properties of Shivagutika, an Indian polyherbal formulation synchronizing in vitro and in silico approaches - V. H., Pushpa; Kuruburu, Mahadevaswamy G.; M. K., Jayanthi; N., Akshaya Simha; Taha Babakr, Abdullatif; Sreenivasan, Rajesh; Ramu, Ramith; Madhunapantula, SubbaRao V. (Frontiers in Chemistry, 2023)
Shivagutika is a polyherbal formulation mentioned in Ayurveda, the oldest system of medicine. The aim of this study was to investigate the anti-breast cancer potential of DCM extract of Shivagutika using MCF-7, MDA-MB-231, and MDA-MB-468. Primarily, various extracts of Shivagutika were prepared and subjected to primary in-vitro analysis – total protein, phenolic acid content, and flavonoid content. DCM extract among all the extracts showed the promising results hence, it was subjected to LC-MS/MS analysis to identify the phytochemicals. The same extract was subjected to anti-proliferation assay and anti-cancer assay. It inhibited all the three cell lines and increased the activity of Caspase 3, pro-apoptotic protein. Further, to find the potent molecule(s) in-silico analysis (molecular docking and molecular dynamics simulation studies) was performed. Sciadopitysin was identified as a potent molecule among all phytochemicals as it interacted with Caspase 3 with a binding energy of -7.2 kcal/mol. MD simulation studies also revealed that Sciadopitysin was stable inside the binding pocket of Caspase -3 by interacting with the amino acids in the catalytic site thereby activating the Caspase 3 levels. By all the above results, Shivagutika could be used as a potent anti-breast cancer agent (specifically DCM extract of Shivagutika) which could decrease the cases of breast cancer in future.